The protective cardiac effects of B-myrcene after global cerebral ischemia/reperfusion in C57BL/J6 mouse - Burcu, Gul Baykalir; Osman, Ciftci; Asl, Cetin; Namik, Oztanir Mustafa; Nese, Basak Turkmen (Acta Cirurgica Brasileira, 2016)
PURPOSE: To investigate the protective effect of beta-myrcene (MYR) on oxidative and histological damage in mice heart tissue caused global cerebral ischemia/reperfusion (IR) in C57BL/J6 mice. METHODS: Animals(n=40) were randomly divided into four groups: (1)control, (2)IR, (3)MYR and (4)MYR+IR. The control group was received 0.1% carboxymethyl cellulose as a vehicle following a medial incision without carotid occlusion. In the IR group, the bilateral carotid arteries were clipped for 15min, and treated with the vehicle intraperitoneally(ip) for 10 days. MYR (200mg/kg) was received dissolved in 0.1%CMC for 10 days. In the MYR+IR group, the IR model was applied exactly as in the IR group, and then they were treated with MYR 10 days. RESULTS: The cerebral IR caused oxidative damage (increase TBARS, decrease antioxidant parameters). Treatment of MYR was increased in GSH,GPx,CAT,SOD activity while TBARS level was decreased. In addition, degenerative changes in I/R group heart tissue were ameliorated by MYR administration. CONCLUSION: The administration of beta-myrcene protects oxidative and histological damage in the heart tissue after global ischemia-reperfusion and may be useful safe alternative treatment for cardiac tissue after ischemic stroke.
Keywords: Brain Ischemia; Reperfusion; Oxidative Stress; Mice